Improving Branding in Namo Mbelin Village UMKM - Nel Arianty (Jurnal Inovasi dan Pengabdian, 2025)
The main problem faced by MSMEs in Namo Mbelin Village is a lack of understanding of the importance of branding and low digital marketing implementation. This program aims to improve the ability of MSMEs to strengthen their brand identity through innovative promotional media and business digitalization. These activities include observation, interviews, outreach, and hands-on practice related to banner creation, business location registration on Google Maps, and digital marketing assistance. These activities have increased the visibility of three fostered MSMEs (Tina Catering, Fotocopy De'Odi, and Toko Munthe), which now have visual identities and digital exposure. Furthermore, these activities, ecoprint tote bags, used cooking oil candle making, and financial literacy, have also strengthened the socio-economic impact of the community. The resulting contribution is seen in the increased competitiveness of MSMEs through branding and sustainable digital innovation.